Metabolically-Healthy Obesity and Coronary Artery Calcification - Chang, Yoosoo; Kim, Bo-Kyoung; Yun, Kyung Eun; Cho, Juhee; Zhang, Yiyi; Rampal, Sanjay; Zhao, Di; Jung, Hyun-Suk; Choi, Yuni; Ahn, Jiin; Lima, João A.C.; Shin, Hocheol; et al. (Journal of the American College of Cardiology, 2014)
The purpose of this study was to compare the coronary artery calcium (CAC) scores of metabolically-healthy obese (MHO) and metabolically healthy normal-weight individuals in a large sample of apparently healthy men and women. The risk of cardiovascular disease among obese individuals without obesity-related metabolic abnormalities, referred to as MHO, is controversial. We conducted a cross-sectional study of 14,828 metabolically-healthy adults with no known cardiovascular disease who underwent a health checkup examination that included estimation of CAC scores by cardiac tomography. Being metabolically healthy was defined as not having any metabolic syndrome component and having a homeostasis model assessment of insulin resistance <2.5. MHO individuals had a higher prevalence of coronary calcification than normal weight subjects. In multivariable-adjusted models, the CAC score ratio comparing MHO with normal-weight participants was 2.26 (95% confidence interval: 1.48 to 3.43). In mediation analyses, further adjustment for metabolic risk factors markedly attenuated this association, which was no longer statistically significant (CAC score ratio 1.24; 95% confidence interval: 0.79 to 1.96). These associations did not differ by clinically-relevant subgroups. MHO participants had a higher prevalence of subclinical coronary atherosclerosis than metabolically-healthy normal-weight participants, which supports the idea that MHO is not a harmless condition. This association, however, was mediated by metabolic risk factors at levels below those considered abnormal, which suggests that the label of metabolically healthy for obese subjects may be an artifact of the cutoff levels used in the definition of metabolic health.